2016
DOI: 10.1007/s40009-016-0489-2
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Method for Propagation of Seabuckthorn (Hippophae rhamnoides L.) by Cuttings

Abstract: One year old growth stem cutting (2.9 ± 0.8 mm thickness), which is less than half of the conventional pencil thickness (7-8 mm) hardwood cutting, was studied for vegetative propagation of seabuckthorn (SBT). Rooting trial tested the effects of 14 media and 6 concentration of indole-3-butyric acid treatment. Over 94 % rooting was observed in all the media tested. The mean rooting percentage was 97.6 ± 2.2. Exogenous auxin treatments lack any benefit and rooting was over 97 % without hormonal treatment. Sevenfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Dale and Galic reported that prechilling of softwood cuttings for 6-8 weeks resulted in dormancy breaking with rooting up to 80% under greenhouse conditions [15] . The hardwood cuttings with less thickness (2.9 mm) showed a sevenfold increase with shooting and rooting in the absence of exogenous hormones [16] . Vegetative propagation from root cuttings and suckers is genetically identical (clones) to the parent plant, and these propagated plants may flower/fruit sooner than seed-propagated plants [13] .…”
Section: Vegetative Propagation In Seabuckthornmentioning
confidence: 93%
“…Dale and Galic reported that prechilling of softwood cuttings for 6-8 weeks resulted in dormancy breaking with rooting up to 80% under greenhouse conditions [15] . The hardwood cuttings with less thickness (2.9 mm) showed a sevenfold increase with shooting and rooting in the absence of exogenous hormones [16] . Vegetative propagation from root cuttings and suckers is genetically identical (clones) to the parent plant, and these propagated plants may flower/fruit sooner than seed-propagated plants [13] .…”
Section: Vegetative Propagation In Seabuckthornmentioning
confidence: 93%
“…First, propagation by a pencil thick hardwood cutting results in fewer cuttings per plant; secondly the rooting success rate is low. Therefore, Dolkar 14 , et al developed an improved method using previous season's growth stem cutting (2.9±0.8 mm thickness) for propagation of SBT. The improved method resulted in much higher rooting percentage than those reported for conventional method using a pencil thick hardwood cutting.…”
Section: Propagationmentioning
confidence: 99%